Graphene oxide / poly (L-lactic acid-co-itaconic acid butanediol ester) copolymer and preparation method thereof

By introducing graphene oxide and unsaturated poly(itaconic acid-co-butylene glycol ester) into PLLA materials, the GO-g-PLBI copolymer was prepared, which solved the problem of insufficient brittleness and heat resistance of PLLA materials. It significantly improves its mechanical properties and barrier properties and broadens its application areas.

CN119219903AActive Publication Date: 2024-12-31INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411519315.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The brittleness, low heat resistance and ultraviolet resistance of PLLA materials limit its further application in the fields of environmental protection and biomedical science.

Method used

GO-g-PLBI was prepared by in situ melt-condensation polymerization of L-lactic acid by using graphene oxide (GO) as initiator and unsaturated poly(itaconic acid-co-butylene glycol ester) PBI as flexible chain segments. Copolymers improve the thermal stability, mechanical properties, anti-aging properties and barrier properties of PLLA films.

Benefits of technology

It significantly improves the thermal stability, tensile strength, elongation of break and ultraviolet barrier properties of PLLA films, while maintaining high transparency, extending the segment branching and micro-crosslinking of the polymer, and enhancing the anti-aging performance. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219903A_ABST
    Figure CN119219903A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials. The invention discloses a preparation method of a graphene oxide / poly (L-lactic acid-co-itaconic acid butanediol ester) copolymer. The preparation method comprises the following steps: S1, preparing a prepolymer of unsaturated poly (itaconic acid-co-butanediol ester); s2, preparing graphene oxide grafted oligomeric (L-lactic acid); and S3, under the assistance of a catalyst (TsOH. H2O and SnCl2. 2H2O), carrying out a melt polycondensation reaction between the prepolymer of the unsaturated poly (itaconic acid-co-butylene glycol ester) and the graphene oxide grafted oligomeric (L-lactic acid) to form a target copolymer. The graphene oxide is used as an initiator, unsaturated poly (itaconic acid-co-butylene glycol ester) is used as a flexible chain segment, and the thermal stability, the gel content, the transparency, the mechanical property, the anti-aging property and the barrier property of the PLLA film are synergistically improved. Therefore, the invention provides an important research thought and direction for developing the polylactic acid nano composite material with adjustable flexibility, excellent oxygen barrier performance, high thermal stability, strong ultraviolet resistance and relatively high transparency, and shows remarkable industrial application potential and value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer and a preparation method thereof. Background Art

[0002] The increasingly serious problem of "white pollution" around the world has posed a significant threat to the natural environment and human living environment. Governments of various countries have introduced plastic restriction policies to reduce dependence on petroleum-based plastic products. In order to solve this global challenge, researchers are actively committed to exploring innovations in the field of biodegradable and renewable materials in order to find effective alternatives to petroleum-based plastics. Among them, biodegradable materials such as polylactic acid (PLA), polybutylene adipate (PBAT), polycaprolactone (PCL), polybutylene succinate (PBS) and polyhydroxyalkanoates (PHAs) have attracted much attention due to their good application potential.

[0003] Among these materials, poly-L-lactic acid (PLLA) has shown broad application prospects in the fields of environmental protection and biomedicine due to its excellent biodegradability, biocompatibility, balanced mechanical properties and wide applicability of manufacturing processes. However, the inherent brittleness, low heat resistance and UV resistance, as well as moderate gas barrier properties of PLLA have limited its further promotion and practical application. Therefore, the development of PLLA materials with excellent mechanical properties, barrier properties and anti-aging properties has become an urgent need for current research.

[0004] In order to improve the comprehensive performance of PLLA film, researchers have conducted in-depth exploration on precursor selection and synthesis routes. On the one hand, L-lactide can generate high molecular weight PLLA through ring-opening polymerization, but the monomer cost is high and the synthesis process is complicated. In contrast, lactic acid, as another synthetic monomer, has a more abundant source, lower cost, and is easy to modify, which provides the possibility of improving the comprehensive performance of PLLA. Through the ring-opening polymerization (ROP) of lactide and the condensation reaction of lactic acid, combined with the use of multifunctional initiators such as polyols, polyacids and nanomaterials, multi-branched PLLA has been successfully developed, effectively enhancing the functionality of its structure.

[0005] It is worth noting that the PLLA nanocomposite formed by combining PLLA with a small proportion of nanofillers is expected to show the characteristics of a high-performance new biodegradable and biocompatible composite material. In situ polymerization is an effective method to achieve uniform dispersion of fillers in the matrix and produce good interfacial interactions with the main polymer. However, the one-step synthesis of high molecular weight multi-branched PLLA based on nanomaterials is still limited by harsh conditions and expensive precursors (such as lactide).

[0006] Graphene oxide (GO), as an oxidized derivative of graphene sheets, contains a variety of hydrophilic functional groups (such as hydroxyl or epoxy groups on the base surface, carbonyl or carboxyl groups on the edge), making it easy to disperse in water and polar solvents. This property facilitates the further modification and subsequent processing of GO.

[0007] However, to date, there has been no report on the simultaneous introduction of poly (itaconic acid-co-butylene glycol ester) (PBI) and GO to synergistically improve the thermal stability, gel content, transparency, mechanical properties, anti-aging properties and barrier properties (including gas and UV barrier properties) of PLLA films. In-depth exploration of this research field is expected to open up a new path for improving the performance of PLLA materials and expanding their application areas. Summary of the invention

[0008] In view of this, the present invention proposes for the first time a method of using GO as an initiator and unsaturated PBI as a flexible segment to synthesize GO-g-poly(L-lactic acid-co-butylene itaconate) (GO-g-PLBI) copolymers through in-situ melt polycondensation of LA (L-lactic acid). The present invention also reveals the specific effects of the introduction of GO and PBI on the thermal stability, gel content, transparency, mechanical properties, anti-aging properties and barrier properties (including gas and UV barrier properties) of PLLA films. Therefore, the present invention not only provides a new way to synthesize low-cost, environmentally friendly and high-performance graphene oxide / poly(L-lactic acid-co-butylene itaconate) copolymers, but also provides important research ideas and directions for the development of polylactic acid nanocomposites with adjustable flexibility, excellent oxygen barrier properties, high thermal stability, strong UV resistance and high transparency.

[0009] The technical solution of the present invention is achieved in this way:

[0010] The first invention provides a method for preparing a graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, S1, mixing itaconic acid and 1,4-butanediol, reacting at 145-155°C and nitrogen atmosphere for 1.5-2.5h under the action of an inhibitor, and then heating at 40-80

[0011] Pa and continue the reaction at 145-155° C. for 5-7 hours to obtain product A; the number average molecular weight of the product A is 800-2000;

[0012] S2, mixing L-lactic acid and monolayer graphene oxide powder, and ultrasonicating for 0.5 to 1.5 h to uniformly disperse the graphene oxide in the L-lactic acid,

[0013] React at 105-115°C and 35-45 kPa for 0.5-1.5 h, then reduce the pressure to 10-16 kPa, and react at 145-155°C for 1.5-2.5 h.

[0014] Then the pressure is reduced to 2-6 kPa, and the reaction is carried out at 145-155°C for 3-5 hours to obtain product B;

[0015] S3, A, B and a catalyst are mixed, and the reaction is carried out at a vacuum degree of 40 to 80 Pa and 175 to 185° C. for 18 to 22 hours to obtain a product C; then the temperature is reduced to 165 to 175° C., a chain extender is added, and the reaction is continued to obtain a product D; after the product D is crushed, it is crystallized at a vacuum degree of 50 to 70 Pa for 2 to 4 hours, and then solid-phase polymerization is carried out at a temperature 5 to 15° C. lower than its melting point for 44 to 52 hours to obtain the graphene oxide / poly (L-lactic acid-co-butylene glycol itaconate) copolymer;

[0016] The product A is a prepolymer of unsaturated poly (itaconic acid-co-butylene glycol ester);

[0017] The product B is graphene oxide grafted oligo(L-lactic acid). In the step S2, a polycondensation reaction occurs between the hydroxyl groups of L-lactic acid to form an oligo(L-lactic acid) chain. Graphene oxide serves as an initiator, and the functional groups on the surface of graphene oxide react with the functional groups at the ends of L-lactic acid or the oligo(L-lactic acid) chain.

[0018] In some preferred embodiments, in step S1, the molar ratio of itaconic acid to 1,4-butanediol is 1:1.03.

[0019] In some preferred embodiments, in step S1, the polymerization inhibitor is hydroquinone, and the mass ratio of hydroquinone to itaconic acid is 1:200.

[0020] In some preferred embodiments, in step S2, the mass ratio of the L-lactic acid to the single-layer graphene oxide powder is 10000:1.

[0021] In some preferred embodiments, in step S2, the single-layer graphene oxide powder is a single-layer graphene oxide nanosheet with a sheet diameter ranging from 5 to 10 μm and a thickness of 0.55 to 2.35 nm.

[0022] In some preferred embodiments, in step S3, the catalyst is SnCl2·2H2O and TsOH·H2O mixed in an equal molar ratio; the added amount of SnCl2·2H2O is 0.5wt% of the total reactants.

[0023] In some preferred embodiments, in step S3, the chain extender is triphenyl phosphite, and the mass ratio of the chain extender to the product C is 1:40. After adding the chain extender, the reaction is continued for 2.5 to 3.5 hours at a vacuum degree of 25 to 35 Pa to obtain product D.

[0024] In some preferred embodiments, the step S3 further includes the following steps: after obtaining the graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, dissolving it in an organic solvent, precipitating it with icy ethanol, and finally vacuum drying it for 44 to 52 hours.

[0025] Terminology Note:

[0026] abbreviation the term GO Graphene oxide LA L-Lactic Acid I A Itaconic acid BDO 1,4-Butanediol PLLA Poly (L-lactic acid) OLLA Oligo(L-lactic acid) PBI Poly(itaconate-co-butylene glycol) PLBI Poly (L-lactic acid-co-butylene itaconate) PVA-g-AC Polyvinyl alcohol-g-acryloyl chloride GO-g-OLLA GO-g-oligo(L-lactic acid) GO-g-PLBI GO-g-poly(itaconate-co-butylene glycol) GO-g-PLLA GO-g-poly (L-lactic acid) TPP Triphenyl phosphite

[0027] PBI :It is an unsaturated polyester. Unsaturated PBI has excellent performance as a flexible chain segment due to its isolated double bonds and aliphatic polyester skeleton in its molecular structure and the characteristics of unsaturated polyester.

[0028] co : represents the copolymer unit in the copolymer.

[0029] g : Indicates graft.

[0030] Prepolymer : It refers to a low degree of polymerization intermediate that can be converted into a high molecular weight polymer. Its number average molecular weight (Mn) is generally several hundred to several thousand. The conversion is carried out through the reaction of terminal or side functional groups and is carried out simultaneously with the cross-linking reaction.

[0031] Oligomer : Represents a polymer composed of a smaller number (generally 10 to 20) of repeating units.

[0032] Copolymer : refers to a polymer produced by copolymerization of two or more monomers.

[0033] In some embodiments of the present invention, the GO-g-PLBI copolymer is copolymerized by GO-g-OLLA and PBI, thereby synthesizing the target copolymer GO-g-PLBI.

[0034] Micro-cross-linking : refers to the introduction of a small amount of cross-linking bonds between copolymer segments, so that a tiny cross-linking network is formed between the segments. In the copolymer, different monomer units are connected together in a random, alternating, block or grafting manner to form a complex chain structure.

[0035] In-situ polymerizationIn-situ polymerization is a method for preparing composite materials, in which fillers (such as reinforcement materials, nanoparticles, etc.) are uniformly dispersed in a matrix material (usually a polymer). Through polymerization, chemical bonds or other strong interactions are generated between these fillers and the main polymer, thus forming a more compact and stable interface.

[0036] Melt polymerization, in-situ melt polycondensation :The melt polymerization method is that the monomer (or oligomer) is heated to an appropriate temperature in a molten state to initiate the polymerization reaction. The in-situ melt polycondensation method combines the ease of operation of the melt polymerization method with the high molecular weight generation characteristics of the polycondensation reaction.

[0037] In some embodiments of the present invention, GO-g-PLBI was successfully prepared by in-situ melt polycondensation of LA using GO as an initiator and PBI as a flexible segment. Specifically, the process is to introduce an unsaturated PBI block on the basis of GO-g-OLLA by melt polymerization to synthesize the target copolymer GO-g-PLBI.

[0038] During the melt polycondensation reaction, the hydroxyl or carboxyl groups at the ends of the unsaturated PBI molecules copolymerize with the functional groups in GO-g-OLLA to form stable chemical bonds. At the same time, the unsaturated double bonds in PBI also participate in cross-linking and branching reactions, further enhancing the network structure and properties of the copolymer. This achieves an effective combination of GO and PBI at the molecular level, and also gives the copolymer higher reactivity and more complex structural properties.

[0039] The specific reaction principle of the present invention includes the following:

[0040] Step S1, a polycondensation reaction occurs, and the unsaturated carbon-carbon double bonds in IA undergo an esterification reaction with the hydroxyl groups of BDO to form a polymer chain. Hydroquinone controls the degree of polymerization. The structure of the generated PBI prepolymer is as follows:

[0041]

[0042] Among them, the range of y is 5 to 20

[0043] In step S2, polycondensation reaction occurs between the hydroxyl groups of LA to form oligolactic acid chains. At the same time, GO acts as an initiator, and the functional groups on the surface of GO react with the functional groups at the ends of the LA or OLLA chains to graft the GO nanosheets onto the OLLA chains. This grafting reaction may occur at multiple locations of GO to form multiple grafting points, thereby uniformly dispersing the GO nanosheets in the OLLA matrix. Therefore, the chemical structure of the GO-g-OLLA prepolymer may contain multiple OLLA segments, which are connected to the functional groups on the surface of the GO nanosheets through ester bonds or other types of chemical bonds. The entire structure may present a three-dimensional network structure in which GO nanosheets are dispersed in the OLLA matrix.

[0044] GO-g-OLLA prepolymer, i.e. GO grafted oligo(L-lactic acid), has the following structural formula:

[0045]

[0046] Where x is 80 to 211

[0047] In the reaction process of step S3, GO acts as an initiator to promote the in-situ melt polycondensation reaction of unsaturated PBI and LA, and finally synthesizes GO-g-PLBI copolymer. In this process, GO not only acts as a physical support point, but also chemically bonds with the terminal functional groups of the reactant chain segments through its surface active functional groups (hydroxyl, carboxyl, etc.), thus achieving the firm grafting and uniform dispersion of GO in the polymer matrix.

[0048] Furthermore, with the assistance of catalysts (TsOH·H2O and SnCl2·2H2O), the reaction system effectively promoted the melt polycondensation between GO-g-OLLA and PBI prepolymer, and through the reaction of terminal hydroxyl or carboxyl groups, alternating or randomly distributed PLLA segments and PBI segments were formed. These segments were tightly connected by ester bonds, constructing the main chain structure of the copolymer.

[0049] TPP effectively extends the length of the polymer chain by reacting with the unreacted functional groups at the end of the polymer chain, thereby significantly increasing the molecular weight of the copolymer.

[0050] The unsaturated carbon-carbon double bonds in the PBI molecules show high reactivity under high temperature conditions. They can undergo cross-linking and branching reactions. These reactions not only increase the cross-linking and branching degree of the copolymer, but also promote the formation of a three-dimensional network structure, further enhancing the structural stability and thermal stability of the copolymer.

[0051] Although most of the terminal functional groups will participate in the reaction during the reaction, some of them may still remain in the copolymer, and these functional groups may have an impact on the further modification or application of the copolymer.

[0052] GO-g-PLBI, namely graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, has the following structural formula:

[0053]

[0054] In a second aspect, the present invention provides a graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer prepared according to any one of the above preparation methods.

[0055] In a third aspect, the present invention further provides a graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer film, the raw materials of which include the graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer.

[0056] The beneficial effects of the present invention include at least the following:

[0057] The present invention uses GO as an initiator in the LA polycondensation process, which not only promotes the uniform dispersion of graphene nanosheets in the polymer matrix, but also promotes the formation of a multi-branched structure. This feature significantly improves the thermal stability, tensile strength, elongation at break (EB), and UV and oxygen barrier properties of the film, while maintaining a high transparency of 76.8%.

[0058] By introducing unsaturated PBI into the GO-g-PLLA chain segment, the branching degree of the chain segment was further improved, the molecular weight of the polymer was increased, and the micro-crosslinking of the copolymer chain segment was promoted. This micro-crosslinking structure not only improves the dispersibility of graphene nanosheets in the polymer, but also significantly enhances the mechanical properties of the film. Compared with pure PLLA, the EB of the GO-g-PLBI film increased by 73.8 times, and the oxygen permeability coefficient (OP) decreased by 40.3%.

[0059] In addition, aging test results show that the GO-g-PLBI film can still maintain considerable flexibility after being stored under ambient conditions for 170 days, and its EB can reach 199.8%. This excellent anti-aging performance is closely related to its higher segment branching degree and micro-cross-linking phenomenon, which hinder the orderly rearrangement of the two-dimensional and three-dimensional conformations of the film.

[0060] It is worth noting that after physical aging treatment, the OP of this micro-crosslinked GO-g-PLBI film further decreased by 60.9%, showing extremely high oxygen barrier performance. This discovery provides a new idea for the development of high-performance oxygen barrier materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0062] Figure 1 is the nuclear magnetic resonance (NMR) spectra of the PLLA, GO-g-PLLA and GO-g-PLBI copolymers of the present invention, wherein: (a) 1 H-NMR; (b) 13 C-NMR; (c) 2D HSQC spectrum;

[0063] Figure 2 The attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectra of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention are shown in Figure 1; wherein: (a) the ATR-FTIR spectrum of the copolymer film and (b) the ATR-FTIR spectrum of the copolymer film at 1849-1630 cm -1 and (c) 831-800cm -1 Local enlarged FTIR spectrum at ;

[0064] Figure 3 The X-ray photoelectron spectroscopy (XPS analysis) diagram of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention; wherein: (a) XPS measurement scans of copolymer films and GO and (b) C1s spectra. (b) GO; (c) PLLA; (d) GO-g-PLLA; (e) GO-g-PLBI;

[0065] Figure 4 The thermogravimetric and gel content analysis diagrams of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention; wherein: (a) thermogravimetric (TGA) curve of the copolymer; (b) solubility (dispersion) characteristics of the copolymer in chloroform; (c) insoluble matter content of the copolymer;

[0066] Figure 5 The stress-strain curves, tensile strength (TS) and elongation at break (EB) of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention at different aging times (0, 50 and 170 d); wherein: the stress-strain curves and mechanical parameters of the copolymer films stored under ambient conditions for (a) 0, (b) 50 and (c) 180 d, respectively; (d) tensile strength; (e) elongation at break;

[0067] Figure 6The SEM images of the tensile fracture surfaces of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention at 0 (1), 50 (2) and 170 (d) aging times, wherein: (a) PLLA; (b) GO-g-PLLA; (c) GO-g-PLBI;

[0068] Figure 7 The temperature-dependent Fourier transform infrared spectra (a1-c1) and difference spectra (a2-c2) of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention are recorded by heating the copolymers from 30°C to 90°C at a rate of 6°C / min at 1800-1720 cm -1 The spectrum collected in the range was calculated by subtracting the spectrum collected at 30 °C, where (a) PLLA; (b) GO-g-PLLA; (c) GO-g-PLBI; (d) 1758 cm-1 calculated according to (ac) -1 (d), 1745 (e) and 1261 cm -1 The normalized intensity of the peak at (f) varies with temperature;

[0069] Figure 8 DSC temperature rise curves and corresponding thermodynamic parameters of PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention aged at 0 (a), 50 (b) and 170 d (c) in the range of 0 to 70 °C under ambient conditions, wherein: (d) Tg; (e) ΔHr;

[0070] Fig. 9 The wide-angle X-ray diffraction (WXRD) patterns of PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention aged at 0 (a), 50 (b) and 170 d (c) under ambient conditions;

[0071] Fig.10 UV-visible spectra of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention (a); light transmittance evaluation of the films under natural light conditions (b);

[0072] Fig.11 The oxygen permeability properties (a, b) of the PLLA, GO-g-PLLA and GO-g-PLBI copolymer films of the present invention and the TEM images (cf) of the copolymers; wherein: (a) oxygen permeability (OTR); (b) oxygen permeability coefficient (OP); (c) TEM image of GO-g-PLLA film and (d) a local enlarged image; (e) TEM image of GO-g-PLBI film and (f) a local enlarged image. DETAILED DESCRIPTION

[0073] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0074] Example 1 Preparation of GO-g-PLBI copolymer

[0075] 1. Preparation of PBI prepolymer

[0076] Itaconic acid (IA) and 1,4-butanediol (BDO) were mixed in a molar ratio of 1:1.03, and 0.5 wt% of hydroquinone was added as a polymerization inhibitor relative to IA. The mixture was reacted at 150°C and nitrogen atmosphere for 2 h. The reaction was then continued at 60 Pa and 150°C for 6 h to obtain a PBI prepolymer (Mn number average molecular weight = 95).

[0077] 2. Preparation of GO-g-OLLA prepolymer

[0078] 700g of L-lactic acid (LA) and 0.01wt% of monolayer GO powder (sheet diameter 5-10μm, thickness 0.55-1.45nm) relative to LA were added to a four-neck open reactor (the four-neck open reactor was connected to a reaction system equipped with a mechanical stirring device, a condensation circulation device and a water removal device). The mixture was ultrasonicated for 1h to achieve uniform dispersion of GO in LA. The reaction was carried out at 110℃ and 40kPa for 1h. The pressure was then reduced to 13kPa and reacted at 150℃ for 2h. The pressure was then reduced to 4kPa and reacted at 150℃ for 4h to obtain GO-g-OLLA prepolymer.

[0079] 3. Preparation of GO-g-PLBI copolymer

[0080] GO-g-OLLA was mixed with PBI prepolymer (5.0 wt% relative to GO-g-OLLA), SnCl2·2H2O and p-toluenesulfonic acid monohydrate (TsOH·H2O, CAS NO: 6192-52-5). The amount of SnCl2·2H2O added was 0.5 wt% of the total reactants. TsOH·H2O and SnCl2·2H2O were mixed in an equal molar ratio. The pressure in the reactor was reduced to 60 Pa within 60 min, and the mixture was reacted at 180° C. for 20 h to obtain a crude product. The reaction system was reduced from 180° C. to 170° C., and 2.5 wt% of triphenyl phosphite (TPP, CAS NO: 101-02-0) relative to the crude product was added, and the reaction was continued at 30 Pa for 3 h to obtain a chain-extended product. The chain-extended product was crushed, crystallized at 60 Pa and crystallization temperature for 3 h, and then solid-phase polymerized at a temperature 10° C. below the melting point for 48 h. The GO-g-PLBI copolymer was obtained by dissolving it in chloroform, precipitating it with ice ethanol, and drying it in vacuum for 48 h.

[0081] Comparative Example 1 Preparation of GO-g-PLLA

[0082] Comparative Example 1 is intended to synthesize GO-g-PLLA by the method of Example 1, but omitting the addition of PBI prepolymer and TPP.

[0083] 1. Preparation of GO-g-OLLA prepolymer

[0084] 700 g of L-lactic acid (LA) and 0.01 wt% monolayer GO powder relative to LA were added to a four-neck open reactor (the four-neck open reactor was connected to a reaction system equipped with a mechanical stirring device, a condensation circulation device and a water removal device). The mixture was ultrasonicated for 1 hour to achieve uniform dispersion of GO in LA. The reaction was carried out at 110°C and 40 kPa for 1 hour. The pressure was then reduced to 13 kPa and reacted at 150°C for 2 hours. The pressure was then reduced to 4 kPa and reacted at 150°C for 4 hours to obtain a GO-g-OLLA prepolymer.

[0085] 2. Preparation of GO-g-PLLA

[0086] Catalysts TsOH·H2O and SnCl2·2H2O were added to GO-g-OLLA. The amount of SnCl2·2H2O added was 0.5wt% of the total reactants, and TsOH·H2O and SnCl2·2H2O were mixed in equal molar ratios. The pressure in the reactor dropped to 60Pa within 60min, and the mixture was reacted at 180℃ for 20h to obtain a crude product. The crude product was dissolved in chloroform, precipitated with ice ethanol, and vacuum dried for 48h to obtain GO-g-PLLA.

[0087] Comparative Example 2 Preparation of PLLA

[0088] 700g of L-lactic acid (LA) was added to a four-neck open reactor (the four-neck open reactor was connected to a reaction system equipped with a mechanical stirring device, a condensation circulation device and a water removal device). The reaction was carried out at 110°C and 40kPa for 1h. The pressure was then reduced to 13kPa and the reaction was carried out at 150°C for 2h. The pressure was then reduced to 4kPa and the reaction was carried out at 150°C for 4h to obtain an OLLA prepolymer. Catalysts TsOH·H2O and SnCl2·2H2O (TsOH·H2O and SnCl2·2H2O were mixed in equal moles) were added to OLLA. The amount of SnCl2·2H2O added was 0.5wt% of the total reactants. TsOH·H2O and SnCl2·2H2O were mixed in equal molar ratios. The pressure in the reactor was reduced to 60Pa within 60min. The mixture was reacted at 180°C for 20h to obtain a crude product. The crude product was dissolved in chloroform, precipitated with icy ethanol, and dried in vacuum for 48 h to obtain GO-g-PLLA.

[0089] Example 2

[0090] After dissolving 2.80 g of the raw material (GO-g-PLBI copolymer obtained in Example 1) in 70 mL of chloroform, a GO-g-PLBI thin film with a thickness of about 60.0±2.0 μm was prepared by a solution casting method.

[0091] For comparison, GO-g-PLLA film and PLLA film were prepared by the same method (the raw materials were replaced by the corresponding products of Comparative Example 1 or 2 above).

[0092] All films were stored at room temperature under vacuum for 10 days to remove the residual solvent in the films.

[0093] 1. Nuclear magnetic resonance (NMR) detection of three copolymers of PLLA, GO-g-PLLA and GO-g-PLBI

[0094] The chemical structure and polymerization results of the copolymers were confirmed by NMR spectroscopy (400 Hz Avance 2B Bruker, Germany) at 25 °C using CDCl3 as solvent. 1 H NMR scan, 1024 times 13 C-NMR scan.

[0095] like Figure 1 As shown, through 1 H-NMR and 13 C-NMR inferred the chemical structure information of the copolymer. We successfully predicted the possible chemical structures of PLLA, GO-g-PLLA and GO-g-PLBI copolymers based on the relevant chemical shift values. Figure 1 (a)1 From the H-NMR spectrum, it can be seen that for PLLA, the peaks at δ = 5.18 and 1.59 ppm belong to the proton signals of the methine (a, -CH-) and methyl (b, -CH3), respectively. For GO-g-PLLA and GO-g-PLBI, in addition to the typical methine (a, -CH-) and methyl (b, -CH3) proton signals, weaker proton signals also appeared at 2.44 ppm and. In addition, for GO-g-PLBI, the peaks at δ = 1.71 ppm and 4.15 ppm belong to the -CH2- (f) and -O-CH2- (g) proton peaks of the BDO domain, respectively. The multiple peaks at 3.47-5.31 ppm are attributed to the methylene protons (d, -CH2-) in the IA domain. The multiple peaks of δ = 6.33-6.47ppm and 5.74-5.87ppm are attributed to the protons of the side chain olefins (e, CH2 = C-) provided by IA and the olefins (e, -CH = C-) after the addition of the side chain olefins. The actual mass ratio of the PBI block in the GO-g-PLBI copolymer was calculated to be 5.3% using the integral area of ​​the -O-CH2-protons (δ = 4.15ppm) in the BDO structural unit and the -CH-protons (δ = 5.16ppm) in the LA structural unit using formula (1), which is consistent with the expected feed ratio.

[0096]

[0097] Among them I d and I a Corresponds to 1 The integrated area at the marked point in the H-NMR spectrum. Interestingly, the vinyl proton peaks at δ = 6.43 and 5.83 ppm in GO-g-PLBI are significantly lower than the intensities of vinyl hydrogen protons at δ = 6.30 and 5.70 ppm. And it is assumed that all vinyl groups in the copolymer are side chain olefins (CH2 = C-). Ideally, the molar ratio of BDO structural units to vinyl groups in PBI is 1:1. That is, the integral area ratio of -O-CH2- protons to the integral area ratio of side chain olefin (CH2 = C-) protons is 2:1. However, in reality, the molar ratio of the integral area of ​​-O-CH2- protons to olefin protons in the BDO structural unit is 100:37. The above phenomenon indicates that there is a certain degree of consumption of carbon-carbon double bonds in the copolymer. In addition, the degree of branching of unsaturated bonds was further calculated using formula (2) to be 30.3%. In particular, the peaks appearing at δ = 7.81-7.82, 7.33-7.40 and 7.07-7.09 ppm may be related to the hydrogen protons on the phosphine structure at the end of the copolymer molecular chain after chain extension.

[0098]

[0099] like Figure 1(be) as shown, further use 13 C-NMR spectrum and 2D-HSQC were used to correlate and confirm the structural information of the copolymer. As shown in the figure, the peak at δ = 169.53 ppm is caused by the carbonyl group (1, -CO) of PLLA. Combined with 2D-HSQC ( Figure 1 As shown in (c), the appearance of (a, 2, -CH-) and (b, 3, -CH3) confirms the typical structure of PLLA. For GO-g-PLLA, in addition to the typical PLLA main chain structure, unsaturated carbon signals (4, ) and the saturated carbon signal caused by defects (6). At the same time, combined with 2D-HSQC ( Figure 1 (d)) shows that there is a weak unsaturated carbon signal (a, 5) connected to hydrogen protons. For GO-g-PLBI, in addition to the typical GO-g-PLLA main chain structure, there are also (e, 9, CH2 = C-, IA), (e, 10, C-CH = C-, IA) (f, 11, -O-CH2-, BDO) and d, 6 (g, 12, -CH2-, BDO) positions, indicating that PBI was successfully synthesized onto the GO-g-PLLA main chain.

[0100] 2. Gel Permeation Chromatography (GPC)

[0101] The number average molecular weight (Mn) and polymer polydispersity index (PDI) of the copolymers were measured by gel permeation chromatography (GPC, LC-20ADXR, Shimadzu Corporation, Japan) with a shodex KF-800 column at 35 °C using chloroform as the mobile phase (1.0 mL / min) relative to calibrated polystyrene standards.

[0102] PDI, the full name of Polydispersity Index, is a quantitative indicator that compares the weight average molecular weight (Mw) and the number average molecular weight (Mn) of a polymer. The calculation formula is PDI = Mw / Mn. The PDI index directly reflects the uniformity of the polymer chain length: the lower the PDI value, the more uniform the distribution of the polymer chain length, and such polymers usually exhibit better overall performance. For high-quality polymer materials, the PDI value is usually between 1 and 2.

[0103] Table 1. Molecular properties of GO nanocomposites

[0104]

[0105]

[0106] Table 1 shows the GPC results of PLLA, GO-g-PLLA and GO-g-PLBI. All three materials have small PDI, indicating that they all have polymer characteristics. n 3.65×10 4 Compared with PLLA, the synthesized GO-g-PLLA has a higher M n (3.89×10 4 g / mol), which may be related to the branched structure induced by GO. After copolymerization of GO-g-OLLA and PBI, the molecular weight of the copolymer further increased to 4.37×10 4 g / mol. This indicates that the introduction of PBI during the melt polycondensation process is beneficial to the formation of high molecular weight PLLA copolymers. The high molecular weight of GO-g-PLBI can be attributed to the long branched structure formed by partial C=C branching reactions between molecular chains, which plays an "internal chain extension" role in the copolymer matrix.

[0107] 3. Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) Spectra of Copolymer Films

[0108] like Figure 2 As shown in Figure 2, the chemical structure information of the copolymer was analyzed by ATR-FTIR. Figure 2 (a) 3250, 1748 and 1616 cm -1 The absorption peaks at 1224 and 1051 cm are related to the stretching vibrations of -OH, C=O and C=C groups of GO, respectively. -1 The absorption peaks at 2995–2850 cm-1 are related to the stretching vibrations of the -CO- and epoxide CO groups, respectively. The typical stretching vibration modes of PLLA were observed in all polymers, including -1 -CH stretching vibration, 1748cm -1 Carbonyl (C=O) stretching vibration, 1180cm -1 The COC symmetric stretching vibration and 1080cm -1 In addition, no characteristic peaks of hydroxyl or carboxyl groups were found, indicating that PBI, GO and TPP were involved in the polycondensation process of L-lactic acid. Figure 2 (bc) shows that the copolymers have the peaks at 1849-1630 cm -1 and 831-800cm -1 The local amplified signal within the range. Figure 2 As shown in (c), compared with PLLA, GO-g-PLLA has a -1 There is a weak peak signal at , which is attributed to the bending vibration of the benzene ring skeleton in graphene. Figure 2 As shown in (b), GO-g-PLBI has a peak at 1748 cm -1 The peak intensity at 1719 cm-1 increased, which may be related to the higher disorder of the GO-g-PLBI copolymer molecular chain. In addition, compared with PLLA and GO-g-PLLA, GO-g-PLBI -1 The peak intensities at 816 cm and 824 cm are larger, which is related to the stretching vibration of the carbonyl group in PBI. -1 The intensity at 177° increased significantly, which is related to the introduction of vinyl groups in PBI. In summary, the above results indicate that GO-g-PLLA and GO-g-PLBI copolymers were successfully synthesized, which is consistent with the results of NMR.

[0109] 4. X-ray Photoelectron Spectroscopy (XPS)

[0110] X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha, USA) was used to analyze the elements and chemical bonding states of GO and film samples. The operation was carried out at 15 kV and 150 W, using a monochromatic Al Kα X-ray source to collect photoelectrons at a take-off angle of 90° relative to the sample surface to obtain scanning measurement spectra of the samples.

[0111] Table 2 Percentages of chemical bonds and elements and binding energies of chemical bonds

[0112]

[0113]

[0114] The XPS spectra and high-resolution C1s XPS spectra of the copolymer films are shown in Figure 2. Figure 3 Table 2 summarizes the bond percentages and binding energies of different bonds based on the C1s spectra of the copolymer films. The C1s spectrum of GO shows three types of carbon bonds, CC / C=C, CO, and OC=O, with binding energies of 284.8, 287.0, and 288.5 eV, respectively. Figure 3(b)). The percentages of CC / C=C, CO and OC=O bonds in GO are 50.2%, 45.1% and 4.6%, respectively (Table 2), and the total oxygen content is 33.36%, indicating a high degree of oxidation. The high-resolution C1s XPS spectra of pure PLLA and copolymers can be deconvoluted into three chemical bonds, namely OC=O, CO and CC / C=C / CH, which appear at binding energies of 289.1-289.2, 287.0-287.2 and 284.8-284.9 eV, respectively. CO (25.0%) and OC=O (23.7%) in PLLA mainly come from the ester group in L-lactic acid. However, the ratio of C to O and the ratio of chemical bonds CC / C=C / CH to OC=O increased from 1.91 and 2.67 in pure PLLA to 2.32 and 4.03 in GO-g-PLLA, respectively, indicating that GO can act as an initiator in the polycondensation process of LA and promote the formation of multi-branched structures. In addition, the relative content of CC / C=C / CH and C / O ratio increased from 65.1% and 2.32 in GO-g-PLLA to 67.5% and 2.40 in GO-g-PLBI, respectively, while the relative content of CO decreased from 18.9% in GO-g-PLLA to 15.8% in GO-g-PLBI. A possible explanation is that the relative content of CC / C=C / CH of PBI units in GO-g-PLBI copolymers is higher, while the relative content of CO is lower, resulting in a higher CC / C=C / CH content and a lower CO content on the surface of the copolymer film. In summary, the above results indicate that GO-g-OLLA was successfully copolymerized with PBI.

[0115] 5. Thermogravimetric analysis

[0116] The thermal stability of the copolymers was evaluated by heating the samples between 30 and 700°C at a rate of 10°C / min using a simultaneous thermogravimetric analyzer (STA, TGA / DSC 1 Mettler-Toledo) under argon atmosphere.

[0117] like Figure 4 (a) is the TGA curve of the copolymer. The main degradation temperature range of pure PLLA is 258.1-313.7℃. The main degradation temperature range of GO-g-PLLA is increased to 260-364.7℃, indicating that GO-g-PLLA has higher thermal stability. This may be because the introduction of GO nanosheets is conducive to heat transfer, thereby improving the thermal stability of the polymer. In addition, it is worth noting that GO-g-PLBI copolymer has higher thermal stability than PLLA and GO-g-PLLA. This may be because the introduction of TPP promotes cross-linking between polymer chain segments and branching between molecular chains, thereby improving the thermal stability of GO-g-PLBI copolymer.

[0118] 6. Gel content

[0119] The gel content of GO-g-PLBI, GO-g-PLLA and PLLA was determined by Soxhlet extraction. Briefly, about 0.3 g of sample was extracted for 24 h using chloroform as solvent. It was then taken out and vacuum dried at 60 °C overnight, and the mass of the residue was finally analyzed. Each sample was measured at least three times. The gel content in the component was calculated using formula (3).

[0120]

[0121] Wherein, m0 is the mass of the residue, M is the mass of the sample before extraction, and m is the gel content in the component. In addition, 0.5 g of the copolymer was accurately weighed and dissolved in chloroform, and the dissolution state of the copolymer was observed with a laser pen.

[0122] To further verify the segment cross-linking phenomenon in the copolymer. Figure 4 (b) is the dissolution (dispersion) characteristics of the copolymer in chloroform. All copolymer solutions showed uniform solutions without obvious precipitation and agglomerates. It should be noted that after laser pen irradiation, PLLA had no obvious micelles, while GO-g-PLLA and GO-g-PLBI both showed micelle phenomena, which was caused by the introduction of GO causing the refraction phenomenon of the copolymer solution. In addition, it should be noted that the micelles in the GO-g-PLBI solution are more obvious. This may be because the unsaturated double bonds in PBI induce partial cross-linking between the copolymer segments, which in turn leads to the enhancement of micelles in the GO-g-PLBI solution.

[0123] like Figure 4 (c) shows the quantitative results of the insoluble matter of the three copolymers. The insoluble matter content of pure PLLA is 0.19%, indicating that there is no obvious interchain crosslinking. The gel content of GO-g-PLLA increases to 0.30%, which may be related to the introduction of GO. In particular, the gel content of GO-g-PLBI increases to 4.99%. This result shows that the introduction of low doses of unsaturated polyesters during melt polycondensation is an effective way to promote micro-crosslinking of polylactic acid.

[0124]

Preparation and performance testing of film aging samples

[0125] The film samples from which the solvent has completely evaporated are stored under ambient conditions for 0, 50 and 170 days respectively to determine the performance indicators of the film. The performance indicators of the film samples stored on the 0th day refer to the data measured when the samples are not aged.

[0126] 7. Tensile properties

[0127] The samples with different aging times were cut into 7cm×0.5cm specimens, and the stress-strain curve of the film was measured using an electronic tensile testing machine (Xn-8750, Labthink, China) with a test area of ​​5mm×28mm and a tensile speed of 10mm / min. The tensile strength (MPa) and elongation at break (%) of the film were obtained from the stress-strain curve. Figure 5 (ac) are shown, (a), (b), and (c) are typical stress-strain curves of PLLA and its copolymer films at different aging times (0, 50, and 170 days). At least 3 repeated tests were performed for each aging time and the average value between each group of repeated tests was taken. The results of tensile strength (TS) and elongation at break (EB) are shown in Figure 5 (de) is shown. The analysis of the measurement results is as follows:

[0128] The TS and EB of unaged pure PLLA are 22.1MPa and 4.6% respectively. During the whole aging period, pure PLLA always shows brittle fracture, and the tensile strength increases gradually, reaching 38.1MPa at 170d.

[0129] The TS and EB of the unaged GO-g-PLLA film were 25.5MPa and 165.4%, respectively, showing a ductile fracture, and showing higher flexibility and strength compared with PLLA. The results show that the introduction of GO can significantly improve the strength and flexibility of PLLA. With the extension of aging time, the initial tensile strength of the GO-g-PLLA film gradually increased, while the elongation at break significantly decreased (p<0.05). At 170d of aging, the EB was only 24.6%, which was only 85.1% lower than that on day 0, indicating that the GO-g-PLLA film has relatively poor anti-aging properties.

[0130] The TS and EB of the unaged GO-g-PLBI film are 13.6MPa and 339.5%, respectively, which is lower than the strength of PLLA, but the EB is about 73.8 times, showing extremely high flexibility. Since the introduction of PBI increases the content of amorphous segments in PLLA, the polymer chain is more effective in local strain transmission during mechanical deformation. In addition, the branched structure in PLBI increases the degree of interchain entanglement, thereby inhibiting the relative slip of the molecular chain during stretching.

[0131] At 50 days, the TS of GO-g-PLBI increased by only 19.8% relative to day 0, while the EB hardly changed (approximately 331.3%);

[0132] At 170 days, TS increased by only 41.2% compared with day 0, while EB decreased by only 41.1%. The above results show that the simultaneous introduction of GO and PBI can significantly improve the tensile properties and long-term physical aging resistance of PLLA.

[0133] It can be seen that GO, as a nanofiller, improves the initial strength and flexibility of PLLA through grafting, but its interaction with the PLLA matrix during aging may be weak, resulting in a significant decrease in EB. At the same time, GO, as a branching site, synergizes with PBI to further enhance the interchain entanglement, thereby inhibiting the relative slip of the molecular chain during stretching, making the GO-g-PLBI film extremely flexible and excellent in anti-aging properties while maintaining high strength. In addition, both pure PLLA and GO-g-PLLA showed unstable performance during aging, especially a significant decrease in EB. In contrast, the GO-g-PLBI film showed less performance change during aging, showing stronger structural stability and resistance to physical aging.

[0134] In the present invention, a very low dose of GO (equivalent to 0.01% (w / w) lactic acid) is used as an initiator, and 5.3% (w / w) PBI is introduced by in-situ polymerization to increase the EB of the film by 73.8 times. A possible explanation is that GO, as an initiator, acts as a branching site during the polymerization of lactic acid, further increasing the degree of interchain entanglement. In addition, as a two-dimensional structure, graphene nanosheets themselves have a certain ductility, and the addition of an appropriate amount of highly dispersed graphene nanosheets can significantly improve the overall tensile properties of the copolymer film.

[0135] 8. Scanning Electron Microscope (SEM)

[0136] A scanning electron microscope (SEM, Regulus 8100, Hitachi, Japan) was used to examine the fracture morphology of the film after the tensile test. The measurement was performed in BSE mode at an accelerating voltage of 15 kV.

[0137] Generally, the compatibility of polymer nanocomposites and the fracture behavior of films can be evaluated by microscopic morphological analysis. Therefore, the fracture surfaces of the stretched specimens were examined using scanning electron microscopy (SEM). In addition, no obvious agglomerates were found on the fracture surfaces of GO-g-PLLA and GO-g-PLBI, and the brightness of the fracture surface was darker than that of PLLA, indicating that GO was successfully and uniformly dispersed in the PLLA and PLBI matrices by in situ polymerization.

[0138] In addition, the fracture surfaces of GO-g-PLLA and GO-g-PLBI showed clear fiber structures, which are typical plastic deformation characteristics, and more obvious in GO-g-PLBI. These results show that GO has a very high compatibility with PLLA and PLBI matrices and can significantly change the fracture behavior of copolymer films. With the increase of aging time, the fiber structure of GO-g-PLLA film gradually decreases ( Figure 6 b(2-3)). This may be due to the aging-induced increase in film crystallinity and decrease in chain integrity, which weakens the deformation ability of GO-g-PLLA and weakens the stress transfer ability of the fiber. In particular, although the fiber coarsening phenomenon appeared on the fracture surface of the GO-g-PLBI film at the late stage of aging (170d), the GO-g-PLBI film showed a clear fiber structure during the entire aging period, indicating that the introduction of PBI can effectively inhibit the decrease in GO-g-PLLA plasticity induced by physical aging, which is consistent with the results of tensile properties.

[0139] 9. Temperature Dependence FT-IR

[0140] The samples were prepared by dropping a certain amount of copolymer chloroform solution on a KBr sheet. After most of the solvent evaporated, the KBr sheet with the sample was placed in a vacuum at room temperature for 48 h to remove the residual solvent. -1 The resolution of 1000 nm was scanned 64 times. The temperature dependence of the KBr sheet with the dried copolymer film was measured by FT-IR (ATR-FTIR, Shimadzu, Japan). The sample was heated to 90°C at a rate of 6°C / min using a hot stage (Caikon, CK-400, Shanghai, China). During this process, the spectrum was collected every 60s in the temperature range of 30-90°C.

[0141] In order to further explore the anti-aging mechanism of GO-g-PLBI film, Figure 7 As shown in (a1-c1), the temperature-dependent infrared spectra and corresponding difference spectra of pure PLLA, GO-g-PLLA and GO-g-PLBI in the carbonyl stretching vibration region and the temperature range of 30-90 °C are depicted, respectively. Figure 7 (a2-c2)). Figure 7 (de) shows that according to Figure 7 (a1-c1) 1758, 1745 and 1261cm -1 The relationship between the normalized intensity of the peaks at 1758, 1745 and 1261 cm and the temperature. -1The absorption peaks at correspond to the gt, tt, and gg conformations of the PLLA molecular chain. Generally speaking, if the polymer has a higher relative content of gt and a lower relative content of gg and gt conformations, the aging phenomenon of the polymer is more serious. Assuming that under the initial conditions, the gt conformation content of pure PLLA, GO-g-PLLA, and GO-g-PLBI is equal ( Figure 7 (d)). Figure 7 As shown in (de), in pure PLLA near the glass transition region, the amount of gt conformation always remains at the highest level, while the amount of gg and tt conformations always remains at the lowest level. In contrast, GO-g-PLBI exhibits the highest levels of gt and tt conformations. Therefore, this result indicates that GO-g-PLBI copolymers exhibit higher segmental mobility and flexibility due to the relatively high initial amount of gg and tt conformations.

[0142] Generally, the content of the energetically favorable conformation in PLLA decreases and the content of the energetically unfavorable conformation increases during heating. It can be observed that as the temperature increases, the 1758 cm -1 The peak intensity at 1745cm decreased, and the peak width increased. -1 The strength of the GO-g-PLLA increases. After the introduction of GO, PLLA exhibits the fastest consumption rate of the gt conformation, while the consumption rate of the gt conformation decreases after the introduction of PBI. Studies have shown that the consumption rate of the gt conformation is higher during heating in the glass transition region, indicating that the polymer is more inclined to rearrange from a high-energy conformation to a low-energy conformation, making it more susceptible to aging. Therefore, the above results indicate that although the introduction of GO by in situ polymerization can increase the degree of disorder of PLLA (higher gg and tt conformational content), it also leads to a faster induction period of gt conformational change, thereby accelerating the aging of GO-g-PLLA. However, after the further introduction of PBI, the induction period of gt conformational change in the copolymer slowed down significantly, thereby reducing the aging rate of the copolymer.

[0143] 10. Differential Scanning Calorimetry (DSC)

[0144] In order to study T g 0.6-0.8 mg of thin film samples were weighed and sealed in aluminum crucibles, and all samples were heated from 0°C to 70°C at a heating rate of 10°C / min in a nitrogen atmosphere.

[0145] like Figure 8 The DSC temperature rise curves in the range of 0-70°C and the corresponding glass transition temperatures (T g ) and thermal relaxation absorption enthalpy (ΔH r ) changes with the number of storage days. It can be found that on the 0th day of storage, all samples have a lower Tg and ΔH r This is because in the early stage of aging, the copolymer molecular chain is in a high energy state, the molecular mobility and densification are low, and the molecular chain is highly disordered, resulting in T g and ΔH r As the storage days increase, the T g and ΔH r This is related to the reduction of free volume due to physical aging. In the period of 0-50d, the T g have similar growth rates, while ΔH r The T values ​​of GO-g-PLLA and PLLA increased by 2.91 and 1.91 J / g, respectively, indicating that GO-g-PLLA film has better anti-aging effect in the range of 0-50 d. On the contrary, in the range of 50-170 d, the T values ​​of GO-g-PLLA are lower than those of PLLA. g and ΔH r The faster growth rate indicates that the accelerated aging period of GO-g-PLLA is after 50 days. The branching effect of the polymer chain induced by GO will make the molecular chain more disordered, resulting in more gg and tt conformations in the polymer. During the solvent-induced aging process, this phenomenon is not conducive to the stability of the polymer conformation, resulting in a longer aging induction period. However, due to the higher rate of gt conformation formation, the aging rate of GO-g-PLLA is relatively fast, resulting in T g and ΔH r The growth rate was even greater in the middle and late stages of aging (50-170 days). It is worth noting that during the entire physical aging process, the T g and ΔH r All of them remain at a low level. First, the introduction of PBI blocks increases the mobility of copolymer segments, which is consistent with previous studies. Second, the copolymers contain relatively more initial gg and tt conformations, which leads to ΔH r The cross-linking phenomenon caused by carbon-carbon double bonds prevents the conformational rearrangement of the GO-g-PLBI chains, resulting in a relatively low ΔH r The rate of change is relatively small.

[0146] 11. Wide Angle X-ray Diffraction (WXRD)

[0147] The WAXD patterns of the film samples and GO powder aged at different times were analyzed by X-ray diffractometer (Rigaku Miniflex 600, Japan) using Cu-Kα radiation. Record. The scanning range is 5°-60° and the scanning speed is 2° / min.

[0148] like Fig. 9The WXRD patterns of the copolymer film after being treated with different aging times are shown in the figure. It can be seen that the observation results show that the pure PLLA without aging treatment exhibits a relatively weak diffraction peak at 2θ=17.02°, which is the characteristic diffraction peak of the (110) / (220) crystal plane in the PLLA crystal. In contrast, the unaged GO-g-PLLA and GO-g-PLBI samples do not show obvious diffraction peaks in this range, indicating that in the unaged state, the crystallinity of GO-g-PLLA and GO-g-PLBI is extremely low or almost non-crystallized. This phenomenon can be attributed to the introduction of GO and PBI as grafting groups, which induces the branching effect of the polymer chain. This branching limits the mobility of the molecular chain segments, thereby inhibiting the formation of a regular crystal structure.

[0149] After aging for 50 days, PLLA showed new diffraction peaks at 2θ=12.42, 19.08 and 21.04°, which were attributed to the (204), (004) / (103) and (203) crystal planes of PLLA, respectively. After aging for 170 days, PLLA showed a diffraction peak of the (015) crystal plane at 2θ=22.56°. With the increase of aging time, the number of diffraction peaks of PLLA gradually increased, the diffraction peak of 2θ=17.02° gradually shifted to the left, and the peak intensity gradually increased, indicating that the crystallinity of PLLA increased after aging treatment. This is because during the aging process, under the action of oxygen, water vapor and light, the molecular chain of PLLA was partially broken, the fluidity was enhanced, and the crystallization rate was accelerated.

[0150] For the GO-g-PLLA film, the diffraction peak intensity at 2θ=17.02° in the early aging period (0-50d) increases more slowly than that in the middle and late aging period (50-170d), and is more obvious than that in the PLLA film aged for 50d. This result indicates that the branching effect induced by GO leads to the formation of more free volume between polymer molecular chains, thereby inhibiting the increase of crystallinity induced by aging.

[0151] It is worth noting that GO-g-PLBI has no diffraction peaks in 0-50d, but a weak diffraction peak appears at 2θ=16.88° at 170d, indicating that the introduction of PBI into GO-g-PLLA will further inhibit the increase in crystallinity induced by physical aging. This is because the branching degree of the copolymer increases after the introduction of PBI, and the microgelation phenomenon exists in the components, resulting in more steric hindrance effects on the rearrangement of the molecular chains, thus greatly inhibiting the increase in crystallinity induced by aging.

[0152] 12. UV-Vis Spectroscopic Analysis of Thin Films

[0153] The UV-visible spectra of the films were measured in the wavelength range of 200-800 nm using a UV-visible spectrophotometer (Cary 5000, Agilent, USA). In addition, optical images of the films were collected under natural light conditions to evaluate the light transmittance of the films.

[0154] Table 3 Quantitative analysis of UV-visible transmittance of GO-g-PLBI copolymer films

[0155] sample UVB (320~400nm) UVA (280~320nm) 600nm PLLA 73.9% 62.1% 85.1% GO-g-PLLA 64.7% 56.4% 76.8% GO-g-PLBI 65.7% 52.7% 76.2%

[0156] like Fig.10 As shown in Table 3, the transparency and UV shielding properties of the GO-g-PLBI copolymer film were evaluated. The transmittance at 600nm is generally defined as visible light transmittance. Ultraviolet rays can be divided into three bands: UVA (320-400nm), UVB (280-320nm) and UVC (200-280nm). Due to the absorption and blocking of the ozone layer, the ultraviolet rays that reach the surface are mainly UVA and UVB.

[0157] As shown in the figure, the pure PLLA film has a high transparency (85.1%), but has poor UV shielding performance. The transparency of the GO-g-PLLA film only dropped to 76.8%, but the UV blocking performance was improved compared to PLLA. This is due to the unique large π conjugated structure of GO nanosheets, which gives it excellent UV absorption ability and high visible light transmittance.

[0158] GO-g-PLBI film has similar visible light transparency as GO-g-PLLA, but has improved UVA light absorption capacity. The transmittance of GO-g-PLBI film at 600nm is 76.2%, which is similar to GO-g-PLLA film (76.8%), and much higher than the UV light transmittance of pure PLLA film, but slightly lower than the visible light transmittance of pure PLLA film (85.1%). GO-g-PLBI film may contain unsaturated PBI blocks, so it exhibits strong absorption capacity for UVB light. In short, compared with PLLA, GO-g-PLBI film has excellent UV absorption and blocking ability, while maintaining a visible light transmittance of 76.2%.

[0159] 13. Oxygen barrier properties and transmission electron microscopy (TEM) testing

[0160] Oxygen permeability was evaluated using a Model 8001 oxygen permeometer. The test was conducted at 23°C and 50% relative humidity. The output pressure of O2 and N2 was set to 0.3 MPa. During the test, the film was placed between two chambers: one chamber was purged with a controlled flow of N2, while the other chamber contained O2. O2 permeated into the N2 carrier gas through the mounted sample and was transported to the coulometric detector, where the amount of O2 flowing into the detector per unit time was calculated. The oxygen permeability rate (OTR) of the film was obtained directly from the test results, and the oxygen permeability coefficient (OP) was calculated using formula (4).

[0161]

[0162] Where D is the thickness of the film, and ΔP is the pressure difference of oxygen inside and outside the film.

[0163] The internal structures of GO-g-PLLA and GO-g-PLBI film samples were analyzed using a field emission transmission electron microscope (TEM, JEM-2100F, Japan Electron).

[0164] OTR is a measurement of the amount of gas that passes through a substrate at a steady rate over a given period of time. Oxygen permeability is an important aspect of controlling the shelf life of food, beverages and goods in packaging applications. When a film exhibits a low OTR value, oxidation is retarded and the shelf life of the product is extended.

[0165] like Fig.11 (ab) shows the results of the changes in OTR and OP values ​​of all films with aging time. It can be seen that the OTR and OP of the unaged PLLA film are approximately 67.9 cm 3 / m 2 d and 1.7×10 -8 cm 3 m / m 2 ·h·Pa, with moderate oxygen barrier properties. With the increase of aging time, the OP values ​​of all samples decreased to varying degrees, and at 170d, the OP values ​​of PLLA, GO-g-PLLA and GO-g-PLBI films decreased by 45.2%, 57.3% and 60.9% respectively compared with the corresponding unaged samples. This result shows that the physical aging process significantly improves the oxygen barrier properties of PLLA and its copolymers, and the effect on GO-g-PLBI and GO-g-PLLA is more significant.

[0166] The decrease in OP value during physical aging is caused by molecular chain rearrangement and free volume reduction. However, it should be noted that the integrity of the polymer segments will be destroyed during physical aging, which has a two-sided effect on the barrier properties. On the one hand, the formation of small molecular segments will act as nucleation sites, leading to an increase in crystallinity, thereby improving the barrier properties of the film. On the other hand, the reduction of macromolecular segments will lead to a decrease in the entanglement of the polymer matrix, which will lead to a decrease in the barrier properties of the PLLA film.

[0167] The decrease in OP value can be attributed to the rearrangement of molecular chains and the reduction of free volume during aging. However, while physical aging enhances barrier properties, it may also destroy the integrity of polymer segments, resulting in a dual effect: on the one hand, small molecular segments act as nucleation sites to promote crystallization and improve barrier properties; on the other hand, the reduction of macromolecular segments may reduce the entanglement of the polymer matrix, thereby weakening the barrier properties.

[0168] The present study shows that the active groups of GO and the carbon-carbon double bonds in the PBI segments as branching sites significantly improve the crosslinking degree of GO-g-PLLA and GO-g-PLBI films, and effectively inhibit the damage to the integrity of the segments caused by physical aging. Although the crystallinity has decreased, this crosslinking effect has greatly reduced the solubility of O2 in the GO-g-PLBI and GO-g-PLLA matrices.

[0169] In addition, the OTR and OP values ​​of GO-g-PLLA and GO-g-PLBI films, whether unaged or aged, are lower than those of PLLA films. This is due to the fact that GO nanosheets are uniformly dispersed in the PLLA and PLBI matrices through in-situ polymerization, which effectively reduces the OP value of the copolymer (e.g. Fig.11 In particular, the OP value of GO-g-PLBI film is lower during aging, which can be attributed to the better dispersion of GO in PLBI matrix (as shown in Fig.11 (d, f)) and the high branching and asymmetry brought by the introduction of PBI increase the polarity of PLLA and reduce the solubility of O2. It is worth noting that the GO-g-PLBI film after aging for 170 days shows a 0.40×10 -8 cm 3 m / m 2 The lowest OP value of ·h·Pa is much lower than that of the reported GO / PLLA nanocomposite films.

[0170] It can be seen that introducing unsaturated polyester into the in situ polymerized graphene / PLLA nanocomposite to promote matrix micro-cross-linking and combining it with moderate physical aging treatment is an effective strategy to simultaneously improve the oxygen barrier properties and ductility of PLLA.

[0171] In summary, the present invention synthesized graphene oxide grafted lactic acid oligomer (GO-g-OLLA) by in-situ polymerization, and then introduced unsaturated PBI blocks by melt polymerization to successfully prepare GO-g-PLBI copolymer. During the polymerization process, the carbon-carbon double bonds of the PBI segments promoted the branching and cross-linking of the copolymer, and this structural change significantly improved the performance of the film. The GO-g-PLBI film showed excellent ductility and UV barrier properties while maintaining high transparency. In addition, the physical aging process affected the structure of the GO-g-PLBI film, and the branching and micro-cross-linking phenomena limited the rearrangement of the segments and enhanced the anti-aging ability of the film. It is worth noting that micro-cross-linking also promoted the dispersion of graphene nanosheets in the PLBI matrix, forming an effective oxygen barrier. Further analysis found that although moderate physical aging treatment caused the oxygen permeability of the GO-g-PLBI film to further decrease, the flexibility remained good. This shows that through reasonable structural design and aging treatment, its oxygen barrier properties can be improved without sacrificing the flexibility of the film. Therefore, the solvent-free polylactic acid copolymerization modification technology proposed in the present invention provides a new way to develop high-performance food packaging materials. The material has excellent performance in oxygen barrier properties, ductility, transparency and anti-aging properties, and has potential application value.

[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, characterized in that: The steps include: S1. Mix itaconic acid and 1,4-butanediol, and react them at 145-155°C in a nitrogen atmosphere for 1.5-2.5 hours under the action of an inhibitor. Then, the reaction is continued for 5 to 7 hours at 40 to 80 Pa and 145 to 155° C. to obtain product A; the number average molecular weight of the product A is 800 to 2000; S2, mixing L-lactic acid and monolayer graphene oxide powder, and ultrasonicating for 0.5 to 1.5 h to uniformly disperse the graphene oxide in the L-lactic acid, React at 105-115°C and 35-45 kPa for 0.5-1.5 h, then reduce the pressure to 10-16 kPa, and react at 145-155°C for 1.5-2.5 h. Then the pressure is reduced to 2-6 kPa, and the reaction is carried out at 145-155°C for 3-5 hours to obtain product B; S3, A, B and a catalyst are mixed, and the reaction is carried out at a vacuum degree of 40 to 80 Pa and 175 to 185° C. for 18 to 22 hours to obtain a product C; then the temperature is reduced to 165 to 175° C., a chain extender is added, and the reaction is continued to obtain a product D; after the product D is crushed, it is crystallized at a vacuum degree of 50 to 70 Pa for 2 to 4 hours, and then solid-phase polymerization is carried out at a temperature 5 to 15° C. lower than its melting point for 44 to 52 hours to obtain the graphene oxide / poly (L-lactic acid-co-butylene glycol itaconate) copolymer; The product A is a prepolymer of unsaturated poly (itaconic acid-co-butylene glycol ester); The product B is graphene oxide grafted oligo(L-lactic acid). In step S2, a condensation reaction occurs between the hydroxyl groups of L-lactic acid to form an oligo(L-lactic acid) chain. Graphene oxide serves as an initiator, and the functional groups on the surface of graphene oxide react with the functional groups at the ends of L-lactic acid or the oligo(L-lactic acid) chain.

2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of itaconic acid to 1,4-butanediol is 1:1.

03.

3. The preparation method according to claim 1, characterized in that: In step S1, the polymerization inhibitor is hydroquinone, and the mass ratio of hydroquinone to itaconic acid is 1:

200.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the L-lactic acid to the single-layer graphene oxide powder is 10000:0.5-3.

5. The preparation method according to claim 1, characterized in that: In step S2, the single-layer graphene oxide powder is a single-layer graphene oxide nanosheet with a sheet diameter ranging from 5 to 10 μm and a thickness of 0.55 to 1.45 nm.

6. The preparation method according to claim 1, characterized in that: In step S3, the catalyst is SnCl2·2H2O and TsOH·H2O mixed in an equal molar ratio; the added amount of SnCl2·2H2O is 0.5wt% of the total reactants.

7. The preparation method according to claim 1, characterized in that: In step S3, the chain extender is triphenyl phosphite, and the mass ratio of the chain extender to the product C is 1:

40. After adding the chain extender, the reaction is continued for 2.5 to 3.5 hours at a vacuum degree of 25 to 35 Pa to obtain product D.

8. The preparation method according to claim 1, characterized in that: Step S3 also includes the following steps: after obtaining the graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, dissolving it in an organic solvent, precipitating it with ice ethanol, and finally vacuum drying it for 44 to 52 hours.

9. A graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 8.

10. A graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer film, characterized in that: The raw materials include: the graphene oxide / poly (L-lactic acid-co-butylene itaconate) copolymer described in claim 9.

Citation Information

Patent Citations

  • Preparation method of polylactic acid functionalized graphene

    CN103086367A

  • Bio-based biodegradable multi-block copolymer as well as preparation method and application thereof

    CN108192105A

  • Long-chain-chain polylactic acid-based copolymer and preparation method thereof

    CN113956486A

  • Preparation method of graphene oxide-polylactic acid composite material

    CN114437318A

  • High-flexibility and high-barrier-property polylactic acid copolymer as well as preparation method and application thereof

    CN117343294A